Application Of Law And Criminal Accountability Against Violent Theft Offenders - Erfan Putra Pratama; Tri Susilowati (Jurnal Indonesia Sosial Sains, 2023)
The components of the wrongdoing of burglary with brutality are referenced in Article 365 of the Lawbreaker Code which should be met, for example in paragraph (1) "followed by violence to facilitate theft", paragraph (2) 1st "the theft was carried out at night", paragraph (2) 2nd "the theft is committed by two or more people together", paragraph (2) 3rd "by breaking or climbing, using fake keys, fake orders, or fake positions", paragraph ( 2) 4th "theft which caused another person to be seriously injured", paragraph (3) "caused death", paragraph (4) "caused another person to be seriously injured or died which was committed by two or more people together". Application of Law and Criminal Accountability Against Violent Theft Offenders in the Central Java Region. As made sense of in the clarification of the Lawbreaker Code (KUHPidana) in regards to the wrongdoing of robbery, it is recognized by different capabilities, incorporating as specified in Article 365 of the Crook Code, in particular burglary forcibly. Burglary with viciousness is a wrongdoing against property. The savagery committed in the robbery has the motivation behind getting ready or working with burglary or on the other hand assuming got there is a chance for the culprit to escape so the taken thing stays in the possession of the culprit. In law and criminal responsibility to perpetrators of theft with violence in the Central Java region. When analyzed by the formulation of offenses contained in the Criminal Code, the above crimes are included in Article 365 of the Criminal Code. It is because there is no definite understanding in the Criminal Code or other laws regarding what robbery, theft and mugging are, but these three forms of crime fulfill the formulation in Article 365 of the Criminal Code, namely theft by force.